Excavations at Brough-on-Humber 1958-61 - Wacher, J.S (Reports of the Research Committee of the Society of Antiquaries of London, 1969)
This is a report of excavations at Brough-on-Humber, England, conducted by J. S. Wacher between 1958 and 1961. Included are descriptions of artefacts such as pottery, coins, buildings and metalwork, together with an account of the methodology used to unearth these.